KONSEP DAKWAH DALAM PENGEMBANGAN MASYARAKAT ISLAM - Nasrl Nasril (Universitas Islam Negeri Imam Bonjol Padang, 2015)
Social history of Muslims is born , grows and develops could not be separated with a history of the rise and fall of social processes Muslims in preaching , theologically considered proselytizing (mission Sacre ) rewarding project and position of propaganda itself is a conditio sine quanon presence , and inherently not be prevented . About this fact should be recognized correctly that the Prophet Muhammad said in his message